Different relation between hypertension and insomnia: an integrative review (Research, Society and Development, 2022)
Introduction: Insomnia and sleep disorders are conditions that damage notably the individuals. Included in this damage there is, possibly, an increase of the mean blood pressure, which can result in Systemic Arterial Hypertension (SAH). The aim of this review is to identify how some qualitative and quantitative sleep variables could change blood pressure, mainly, of insomne people. Methodology: This is an integrative literature review which includes studies with different population groups over time. The databases utilized to collect the articles were Pubmed, MEDLINE and LILACS and only papers published between 2002 and 2022 have been considered. Results: 12 analyzed articles (75%) corroborate the influence of insomnia on blood pressure. In this regard, short sleep, sleep irregularity, difficulty to start and to keep sleep, low ratio of REM sleep to NREM and alteration of autonomic nervous system in the sleep-wake cycle are factors associated with insomnia that have shown potentiality to promove SAH. Conclusion: Although others physiological and social variables impact on blood pressure, it's also necessary to observe sleep influence on the SAH. This is because, of the totality of the articles included in this review, only 25% do not assure the association between insomnia and hypertension. From these data, it is remarkable that quantitative and qualitative aspects of sleep should be focus of hypertension control measures, once SAH is a chronic disease that represents a risk for several cardiovascular disorders.